THE INFLUENCE OF CONTEXTUAL TEACHING AND LEARNING (CTL) APPROACH ON UNDERSTANDING OF MATHEMATICAL CONCEPTS - Winda Dianartasi; Aulia Sthephani (UIR PRESS, 2021)
This study aims to see the effect of using the Contextual Teaching and Learning (CTL) approach on understanding mathematical concepts in class X SMA Negeri 2 Pekanbaru in the 2019/2020 school year. This research is a Quasi Experiment with a Nonequivalent Pretest-Posttest Control Group Design. The population in this study were all students of class X SMA Negeri 2 Pekanbaru with a sample of class X IPS 2 as the experimental class, which was given treatment using the Contextual Teaching and Learning (CTL) approach and class X IPS 3 as a control class using conventional learning. Sampling technique using purposive sampling. Data collection took place from February 14, 2020, to March 4, 2020. The data collection technique in this study was carried out using a test technique. Data were analyzed using inferential analysis. In this study, the data was assumed to be normal; therefore, the inferential analysis carried out only the homogeneity test and t-test. The research results obtained are t-count>t-table. This shows that there is an effect of the Contextual Teaching and Learning (CTL) approach on the ability to understand mathematical concepts in class X SMA Negeri 2 Pekanbaru